Introducción: el giro en el nuevo documental peruano - Godoy, Mauricio (2018)
On June 10, 2003, José Balado inaugurated the Primera Muestra de Documental Peruano. This event is the founding date of contemporary documentary cinema in Peru. The present text seeks to highlight the importance of this event and its impact on the production and reflection around the documentary in Peru.